Learning Arabic Through Virtual Classroom (LAVC) for year six / Muhammad Ajwadi Asnari - Asnari, Muhammad Ajwadi (2023)
The proposed virtual classroom is aimed at addressing the challenges faced by Sekolah Kebangsaan Dato' Yahya Subban, Perak, in teaching Arabic to Year Six students. The study highlights the need for a standardized approach to sharing teaching materials, the impact of e-learning, and the dispersed nature of digital teaching materials. The study proposes using the Universal Design for Learning (UDL) theory and the Adapted System Development Life Cycle (SDLC) method to create a virtual classroom. The phases in the adapted System Development Life Cycle (SDLC) are Planning, Analysis, Design, Development, Implementation, and Report. The virtual classroom was evaluated through a collaborative effort involving a supervisor, IT experts, Arabic specialists, and 30 respondents. The evaluation showed that the virtual classroom effectively meets the requirements and provides a positive learning experience for students in the new elearning environment. Overall, the study highlights the importance of using established theories and models in developing educational technology and the positive impact it can have on student learning.